Spatial distribution of maternal factors in pig mature oocytes - Fuquan Zhu; Meng Yang; Dayu Wang; Yuan Jiang; Chao Jia; Yanfeng Fu; Aochen Yu; Huijun Liu; Meixia Wang; Tingzhang Wang; Honglin Liu; Juan Li (Animal Biotechnology)
It is known that asymmetrical maternal transcripts play an important role in the cell fate of the early embryo, but few studies are available in mammal oocytes especially in pig. To investigate the spatial factors in pig oocytes, the oriented bisection was established for collecting karyoplasts (NSOs) and cytoplasts (SSOs) with more than 95% efficiency. Subsequently, RNA-Seq and LC-MS/MS analysis were performed on NSOs and SSOs. Although no differentially expressed genes (DEGs) could be detected between NSOs and SSOs, 89 of the differentially expressed proteins (DEPs) were detected, that 58 proteins higher expressed but 31 proteins lower expressed in NSOs compared with SSOs. These DEPs mainly participated in the ‘cell cycle’ and ‘ribosome’ pathway, while the up-regulated DEPs were mainly GO in ‘spindle’ and ‘positive regulation of translation’, and the down-regulated DEPs were in ‘cytosolic small ribosomal subunit’ and ‘mRNA binding’. The up-regulated DEP SIRT5 which are related to the regulation of gene expression, epigenetic were further detected and revealed. A spatial asymmetry of maternal factors at the protein level was firstly detected in pig mature oocytes.